Enhancing Students’ Higher-Order Thinking Skills Through Web-Based Learning with Multiple Representations in Biology Education - Toto Sutarto Gani Utari; Cita Tresnawati; Mimi Halimah (Gawi: Journal of Action Research, 2026)
In the digital era, the development of higher-order thinking skills (HOTS) has become one of the major challenges in education, particularly in biology, which requires students to understand complex concepts. This study aimed to analyze students’ higher-order thinking skills (HOTS) through web-based learning integrated with multiple representations in biology education in Bandung, Indonesia. This study employed a one-group pretest–posttest design involving Grade 10 and Grade 11 science-track students selected through purposive sampling from five senior high schools in Bandung, Indonesia. The research instrument consisted of a test comprising both multiple-choice and essay questions. The findings revealed that cognitive ability was the most prominent HOTS dimension, followed by logical analysis, problem-solving, critical thinking, and creative thinking skills. These results indicate that web-based learning integrated with multiple representations can facilitate students’ understanding of biological concepts more effectively. The presentation of various visual representations, including images, three-dimensional animations, videos, tables, diagrams, and graphs, along with case-study features, helped transform abstract content into more concrete and structured forms, thereby strengthening higher-order thinking skills. The findings further suggest that multiple representations enable students to understand biological phenomena from multiple perspectives, critically evaluate information, and apply conceptual knowledge to solve complex problems.